Sport and tourism : globalization, mobility and identity - Higham, James; Hinch, Thomas (Amsterdam : Elsevier Science, 2009)
'Sport and Tourism' proposes a groundbreaking theoretical model which explores globalization, mobility and authenticity providing insight into the unique interrelationship that exists in a sport tourism context between activity, people and place.
Pt. 1. Introduction -- 1. Sport and tourism : globalization, mobility and identity -- -- Pt. 2. Globalization, mobility and identity -- 2. Sport and tourism in a global world -- 3. Sport and contemporary mobility -- 4. Culture and identity -- -- Pt. 3. Activity -- 5. Globalization and the mobility of elite competitors -- 6. Spectatorship and spectator experiences -- 7. Recreational sport and serious leisure -- -- Pt. 4. People -- 8. Authentic experiences -- 9. Temporary sport migrants -- 10. Transnationalism, migration and diaspora -- -- Pt. 5. Place -- 11. Modern landscapes and retro parks -- 12. Place attachment -- 13. Sport and place competition -- -- Pt. 6. Conclusion -- 14. Globalization, mobility and identity : building theoretically informed insights into the study of sport and tourism.
Includes bibliographical references and index.
Keywords: SPORTS AND TOURISM